A Brief review of flood forecasting techniques and their applications. Issue 3 (3rd July 2018) - Jain, Sharad Kumar; Mani, Pankaj; Jain, Sanjay K.; Prakash, Pavithra; Singh, Vijay P.; Tullos, Desiree; Kumar, Sanjay; Agarwal, S. P.; Dimri, A. P.
ABSTRACT: Flood forecasting (FF) is one the most challenging and difficult problems in hydrology. However, it is also one of the most important problems in hydrology due to its critical contribution in reducing economic and life losses. In many regions of the world, flood forecasting is one among the few feasible options to manage floods. Reliability of forecasts has increased in the recent years due to the integration of meteorological and hydrological modelling capabilities, improvements in data collection through satellite observations, and advancements in knowledge and algorithms for analysis and communication of uncertainties. The present paper reviews different aspects of flood forecasting, including the models being used, emerging techniques of collecting inputs and displaying results, uncertainties, and warnings. In the end, future directions for research and development are identified.